Association of Human Antibodies to Arabinomannan With Enhanced Mycobacterial Opsonophagocytosis and Intracellular Growth Reduction. (7th April 2016) - Chen, Tingting; Blanc, Caroline; Eder, Anke Z.; Prados-Rosales, Rafael; Souza, Ana Camila Oliveira; Kim, Ryung S.; Glatman-Freedman, Aharona; Joe, Maju; Bai, Yu; Lowary, Todd L.; Tanner, Rachel; Brennan, Michael J.; et al.
Abstract: Background.  The relevance of antibodies (Abs) in the defense against Mycobacterium tuberculosis infection remains uncertain. We investigated the role of Abs to the mycobacterial capsular polysaccharide arabinomannan (AM) and its oligosaccharide (OS) fragments in humans. Methods.  Sera obtained from 29 healthy adults before and after primary or secondary bacillus Calmette-Guerin (BCG) vaccination were assessed for Ab responses to AM via enzyme-linked immunosorbent assays, and to AM OS epitopes via novel glycan microarrays. Effects of prevaccination and postvaccination sera on BCG phagocytosis and intracellular survival were assessed in human macrophages. Results.  Immunoglobulin G (IgG) responses to AM increased significantly 4–8 weeks after vaccination ( P < .01), and sera were able to opsonize BCG and M. tuberculosis grown in both the absence and the presence of detergent. Phagocytosis and intracellular growth inhibition were significantly enhanced when BCG was opsonized with postvaccination sera ( P < .01), and these enhancements correlated significantly with IgG titers to AM ( P < .05), particularly with reactivity to 3 AM OS epitopes ( P < .05). Furthermore, increased phagolysosomal fusion was observed with postvaccination sera. Conclusions.  Our results provide further evidence for a role of Ab-mediated immunity to tuberculosis and suggest that IgG to AM, especially to some of its OS epitopes, could contribute to the defense against mycobacterial infection in humans.